Human Resource Management in the Development of Teacher Professionalism in Tangerang City - Murniadi; Sutarman (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
Human Resource Management (HRM) plays an essential role in improving the professionalism of teachers, particularly in responding to the increasing demands for educational quality and institutional competitiveness. This study aims to examine the implementation of human resource management in developing teacher professionalism in schools in Tangerang City. The research focuses on several HRM components, including recruitment and selection, training and professional development, performance evaluation, and motivation enhancement. A qualitative approach was employed using data collection techniques such as interviews, observations, and documentation involving school principals, teachers, and education administrators. The findings indicate that effective human resource management contributes significantly to improving teachers’ professional competencies, pedagogical skills, and commitment to educational responsibilities. Training programs, continuous professional development activities, and supportive leadership practices were found to be key factors in strengthening teacher professionalism. Furthermore, systematic performance evaluation and motivational strategies help encourage teachers to enhance their teaching quality and professional engagement. The study concludes that the effective implementation of human resource management practices can support sustainable professional development among teachers and ultimately improve the quality of education in Tangerang City.